Penegakan Hukum Tindak Pidana Korupsi Biaya Pemungutan Pajak Bumi dan Bangunan (PBB) Sektor Perkebunan di Pemerintah Kabupaten Labuhan Batu Selatan - Ane Fransiska Sianipar; Rizkan Zulyadi; Taufik Siregar (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
This study aims to find out and analyze the background, the modus operandi of the Corruption Cases, Land and Building Tax Collection Costs in South Labuhanbatu Regency and to recommend the political concept of criminal law against the abuse of authority by public officials related to corruption cases in Indonesia. The research method that the author uses is normative juridical with a statutory, bibliographical and legal case approach based on secondary data. The data obtained were analyzed by qualitative analysis. The results of the study, the factors causing the occurrence of criminal acts of corruption are due to the abuse of power inherent in him as a regional head, factors of encouragement/persuasion or invitations/suggestions from parties or groups within the Regent's power to act corruptly, as well as factors of gaps or weaknesses law. Related to the administration of PBB collection for the Plantation Sector and the weak rules that emphasize "state losses" in corruption cases. So this, through legal regulations made by the Regent of Labusel as legitimacy for his corrupt actions to harm state finances. The modus operandi of the corruption case was carried out together with the modus operandi of making the Regent's Regulation Number 84 C of 2011 the legal basis for citing PBB of the plantation sector. Criminal Law Politics Against the Abuse of the Authority of Public Officials Related to Corruption Cases in Indonesia can be carried out by penal law enforcement and law enforcement through non-penal means.